Paola Serra Zanetti presenta La Struttura del Gesto : Battaglia - Boero - Carboni - Cortassa - Cotani - Di Palma - Gastini - Griffa - Montessori - Morales - Rampazzi - Rotelli - Sanna - Sassi - Verna - Zucchini. - Serra Zanetti, Paola (Roma : Sala 1, 1987)
Battaglia, Carlo ; Boero, Renata ; Carboni, Luigi ; Cortassa, Nanni ; Cotani, Paolo ; di Palma, Antonio ; Gastini, Marco ; Griffa, Giorgio ; Montessori, Elisa ; Morales, Carmen Gloria ; Rampazzi, Renata ; Rotelli, Marco Nereo ; Sanna, Sandro ; Sassi, Marilena ; Verna, Claudio ; Zucchini, Giorgio
Paola Serra Zanetti presenta La Struttura del Gesto : Battaglia - Boero - Carboni - Cortassa - Cotani - Di Palma - Gastini - Griffa - Montessori - Morales - Rampazzi - Rotelli - Sanna - Sassi - Verna - Zucchini, Sala 1, Roma, dall'8 Febbraio al 2 Marzo 1987
boek